Extrahepatic Malignancy Among Patients With Chronic Hepatitis C After Antiviral Therapy: A Real-World Nationwide Study on Taiwanese Chronic Hepatitis C Cohort (T-COACH). (August 2020) - Huang, Chung-Feng; Lai, Hsueh-Chou; Chen, Chi-Yi; Tseng, Kuo-Chih; Kuo, Hsing-Tao; Hung, Chao-Hung; Wang, Jing-Houng; Chen, Jyh-Jou; Lee, Pei-Lun; Chien, Rong-Nan; Yang, Chi-Chieh; Lo, Gin-Ho; et al.
Abstract : INTRODUCTION: Chronic hepatitis C virus (HCV) infection is associated with nonhepatocellular carcinoma malignancies. We aimed to evaluate whether achieving a sustained virological response (SVR, defined as HCV RNA seronegativity throughout posttreatment 24-week follow-up) could reduce the risk of non–hepatocellular carcinoma malignancy in a real-world nationwide Taiwanese Chronic Hepatitis C Cohort (T-COACH). METHODS: A total of 10, 714 patients with chronic hepatitis C who had received interferon-based therapy (8, 186 SVR and 2, 528 non-SVR) enrolled in T-COACH and were linked to the National Cancer Registry database for the development of 12 extrahepatic malignancies, including those with potential associations with HCV and with the top-ranking incidence in Taiwan, over a median follow-up period was 3.79 years (range, 0–16.44 years). RESULTS: During the 44, 354 person-years of follow-up, 324 (3.02%) patients developed extrahepatic malignancies, without a difference between patients with and without SVR (annual incidence: 0.69% vs 0.87%, respectively). Compared with patients with SVR, patients without SVR had a significantly higher risk of gastric cancer (0.10% vs 0.03% per person-year, P = 0.004) and non-Hodgkin lymphoma (NHL) (0.08% vs 0.03% per person-year, respectively, P = 0.03). When considering death as a competing risk, non-SVR was independently associated with gastric cancer (hazard ratio [HR]/95% confidence intervals [CIs]: 3.29/1.37–7.93, P = 0.008). When patients were stratified by age, the effect of SVR in reducing gastric cancer (HR/CI: 0.30/0.11–0.83) and NHL (HR/CI: 0.28/0.09–0.85) was noted only in patients aged <65 years but not those aged >65 years. DISCUSSION: HCV eradication reduced the risk of gastric cancer and NHL, in particular among younger patients, indicating that patients with chronic hepatitis C should be treated as early as possible.